Critical success factor blockchain technology in renewable energy: systematic literature review - Inayatulloh, Inayatulloh; T., Thoyyibah (International Journal of Reconfigurable and Embedded Systems (IJRES), 2025)
In recent years, blockchain technology has garnered considerable interest in the renewable energy sector. Nonetheless, scholars have yet to investigate the comprehensive assessment of critical success factors (CSFs) for the implementation of blockchain technology in renewable energy. Furthermore, the current research lacks a stage framework or a standardized set of CSFs for blockchain technology. This review study seeks to establish a stage framework and identify a set of common CSFs for the effective adoption of blockchain technology by examining published materials pertinent to the topic under investigation. This evaluation employs a systematic literature review and scientific mapping methodology to objectively ascertain a collection of CSFs. We examined 65 journal articles from the Scopus database and Google Scholar, concentrating on prominent journals, keywords, countries/regions, and documents within the CSF domain of blockchain technology in renewable energy. The findings indicate that nations including China, Australia, the United States, and Germany have made the most significant contributions to this field. Among the 20 CSFs, the foremost five are regulation, integration with current systems, scalability, and security. The proposal delineates four principal research gaps and prospective research trajectories: environmental effect assessment, standardization, user experience and interface design, and management control. The insights and CSF checklist for blockchain technology will facilitate successful exploration and implementation in renewable energy.